O direito à moradia: reinterpretando o conceito de moradia digna - Cazelli, Vinícius Ribeiro (2023)
The present work deals with the interpretation and implementation of the Right to Housing in Brazil, either as a way of defending the vulnerable population that needs it, or as a way of assisting the Public Power in the formulation of adequate and comprehensive public housing policies, especially in view of the necessary interconnection of the rights to housing and health and the importance of joint analysis of such rights. To approach the themes, qualitative and quantitative research of a descriptive nature was used, as well as a dialectical approach, as a means to proceed with the analysis, in a critical way, of the use of the state apparatus, for the maintenance of the ideology of the class dominant, as well as to provide a legal interpretation of the Right to Housing that presents itself as adequate, guarantees the dignity of the citizen and helps in the understanding of the problems faced by the Brazilian population for the realization of this fundamental social right. Housing was also considered as a social determinant of health, given its importance in combating the problems experienced by the Brazilian and world population related to the coronavirus. Documentary research was also carried out to analyze the housing issue in the Municipality of Marataízes/ES, in order to assist in understanding the problems related to land regularization in the municipality and its importance for the health and dignified life of the population. Finally, it was found that the right to decent housing finds support both in the domestic legal system and in the international sphere, however, it lacks an interpretation that expands its effectiveness and transforms the reality experienced by the population. For this to happen, the paths were presented throughout the research and in the final considerations, to assist the public manager in the implementation of the changes that are necessary to guarantee this fundamental social right.